2018
DOI: 10.1186/s13104-018-3899-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of nasal colonization by methicillin-resistant Staphylococcus aureus in outpatients living with HIV/AIDS in a Referential Hospital of the Northeast of Brazil

Abstract: ObjectiveThe purpose of this study is to investigate the prevalence of MRSA among people living with HIV/AIDS (PLHA) being monitored in a tertiary outpatient hospital in the state of Pernambuco, in the Brazilian Northeast.ResultsStaphylococcus aureus was isolated from a nasal swab and found in 31.4% of the individuals (95% CI 27.3–35.5), of whom 4.4% (95% CI 8.5–19.5) were MRSA, as confirmed by the presence of the mecA gene. For individuals whose S. aureus was recovered, the mean age was 41.5 years; 93.6% were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 20 publications
1
8
1
Order By: Relevance
“…Among all MRSA isolates, high drug resistance was observed in penicillin, erythromycin, and clindamycin, which is similar to observed studies [ 4 , 26 , 27 ]. In this study, we believe the MRSA and MRCoNS isolates may show differences in all antibiotic resistance.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Among all MRSA isolates, high drug resistance was observed in penicillin, erythromycin, and clindamycin, which is similar to observed studies [ 4 , 26 , 27 ]. In this study, we believe the MRSA and MRCoNS isolates may show differences in all antibiotic resistance.…”
Section: Discussionsupporting
confidence: 90%
“…As a common cause of severe infections, methicillin-resistant Staphylococcus aureus (MRSA) is still widespread in both health facilities and the community [ 1 , 2 ]. Owing to the compromised immune system, HIV-infected patients are more vulnerable to MRSA colonization than other populations [ 3 , 4 ]. Over the past decade, the prevalence of MRSA isolates and the risk factors associated with MRSA colonization among HIV-infected patients has been reported in many countries and regions except mainland China.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 31 studies, representing a total of 17 427 patients with HIV infection, were selected for the final meta-analysis. 2656 The details of the literature search and study selection are summarized in a PRISMA flow diagram (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…The baseline characteristics of the included studies and recruited patients are presented in Table 1. 2656 Of the 31 included studies, eight had a cohort design, 17 had a cross-sectional design and the remaining six studies had a case–control design. These studies reported a total of 1410 MRSA colonization events and the events of MRSA colonization and infection that occurred in each study ranged from 6 to 252.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation